Study on the association of SLC2A9 rs16890979 with gout in 410 Vietnamese individuals - Thang, Nguyen Tran Minh; Ngoc, Nguyen Thy; Nga, Nguyen Thanh; Hai, Nong Van; Duong, Nguyen Thuy (Academia Journal of Biology, 2021)
Gout is a common form of inflammatory arthritis caused by crystallization of acid uric in the joints. The development of gout is not only triggered by environmental factors but also by genetic variation of individuals. In this study, the association between the variation SLC2A9 rs16890979 and gout was investigated. Total DNA was extracted from 410 blood samples of 163 gout patients and 247 age-matched healthy controls. Genotypes of SLC2A9 rs16890979 were obtained using PCR-RFLP. Chi-Square test was used to test whether allele distribution of rs16890979 followed Hardy-Weinberg Equilibrium (HWE). Associations of the clinical characteristics between gout patient and control groups were assessed using Mann-Whitney U. Chi-Square test or Fisher’s exact test was used to check four models (additive, recessive, dominant, co-dominant) for association of rs16890979 with gout. The obtained results showed that the allele distribution of SLC2A9 rs16890979 was in accordance with HWE (p > 0.05). Clinical characteristics such as triglyceride and creatinine were significantly different between gout patient and control groups. However, there was no association of rs16890979 with the risk of gout in Vietnamese population. Further study with a larger sample size should be implemented to confirm our results regarding the association of SLC2A9 rs16890979 with gout in the Vietnamese population. This study would help enrich the knowledge about the effects of hereditary factors on gout disease in the Vietnamese population.